Analisis Kualitas Layanan pada Bagian Rawat Inap Rumah Sakit di Bandung - Ina Ratnamiasih; Rajesri Govindaraju; Budhi Prihartono; Iman Sudirman (TRIKONOMIKA, 2013)
Hospital has an important role for the growth of a country. Poor of hospital quality care cause public health problems are not immediately addressed. This research aim to have an explanation about inhouse quality of hospital services. However, measurements taken by the patient’s perception produce a picture of the quality of care in hospitals. This research followed an established case study method. A range of general hospital were contacted for this research. The hospitals vary in regards to ownership, as a private and public hospital. Only 6 of 19 hospitals showed interest and willingness to spare part of their time to be observed. The results showed that the quality of hospital services is relatively good. However, there are significant complaints about the lack of time provided by doctors, the hospitals are not continuously provide information about the disease by the patient, including the information of possible complications, and lack of hospital policy to train and give an explanation about disease and pain handling.